If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = 6x + -11 Reorder the terms: -7 + 5x = 6x + -11 Reorder the terms: -7 + 5x = -11 + 6x Solving -7 + 5x = -11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + 5x + -6x = -11 + 6x + -6x Combine like terms: 5x + -6x = -1x -7 + -1x = -11 + 6x + -6x Combine like terms: 6x + -6x = 0 -7 + -1x = -11 + 0 -7 + -1x = -11 Add '7' to each side of the equation. -7 + 7 + -1x = -11 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -11 + 7 -1x = -11 + 7 Combine like terms: -11 + 7 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| -7(x-5)=84 | | 8x-9+13-2x=-36 | | -7n+1-2n+n-4=10 | | 250a+1000b=10000 | | 199-6x=30x+15 | | 3(-2x+4)=42 | | 66x=1 | | 25-2b/7=29 | | 5x-5-3x=-35 | | 55-30q= | | 3x+12=24-6x | | -5/9x-4=-3 | | 91/3+2/3 | | x^2+10=300 | | -37z=259 | | (1/4x)+(1/4x)=4/5 | | 80x-80y=100 | | 2/3(4x-7)= | | 6n-6+3=105 | | 3-12x+12x^2=0 | | 4(g-6)=3G+12 | | 2x+7=10-5x | | -35-4x=5x+10 | | -7z+6=56-2z | | (x-6)/2=75 | | -4+11n=40 | | 4x+62=7x-24 | | 18-(-4y)=8 | | 12a-16=8a+4 | | 5k-1=24 | | y+7(-2)=11 | | B=nx+x |